Exploration and quantification of ascorbate affecting peroxidase-catalyzed chromogenic reactions with a recirculating-flow catalysis detection system. Issue 77 (28th August 2020) - Li, Yong-Sheng; Zhao, Yang; Li, Qiao-Jing; Wang, Ben; Gao, Xiu-Feng
Abstract : This research used a recirculating-flow catalysis detection system to explore the ascorbate interference with peroxidase-catalyzed reactions and simultaneously determined peroxidase and ascorbate with a kinetic curve. Abstract : The use of a recirculating-flow catalysis detection system (RFCD) explored competition and the influence of ascorbic acid (AsA) in peroxidase (POD)-catalyzed reactions. The study identified that AsA is neither the inhibitor of POD nor could directly deplete H2 O2 ; it directly reacts with chromogenic products to form colorless intermediates, which can react with H2 O2 to again rapidly re-generate the chromogenic products. If using the reactions (trinder reactions or enzyme-linked reactions) to determine POD activity ( E POD ), substrates or analytes, the interference of concomitant AsA should be removed and the conclusions have significance for oxidase/POD catalyzed reactions. In addition, the RFCD system was also used to simultaneously determine E POD and AsA.